Perkembangan Tari Kuda Kepang sebagai Media Promosi Wisata Budaya di Kabupaten Kepahiang Provinsi Bengkulu - Niken Novrianti; Eva Riyanti; Rasmida Rasmida; Syahril Syahril (INDO PUBLISHING, 2026)
This study aims to determine the development of the Kuda Kepang Dance as a medium for cultural tourism promotion in Kepahiang Regency, Bengkulu Province. This research employs a qualitative method with a descriptive analysis approach. The results indicate that the Kuda Kepang dance was introduced to Kepahiang Regency in the 1930s through the Javanese transmigration program during the Dutch colonial era. Since 2023, the dance has undergone significant development led by choreographer Eigmal, who implemented creative reconstructions and innovations across movement elements, musical accompaniment, dancers, makeup, costumes, properties, floor patterns, and performance venues. Despite these modern modifications to suit contemporary entertainment and aesthetic demands, the Kuda Kepang dance preserves its core values and traditional roots. Furthermore, the dance effectively serves as a promotional tool for regional cultural tourism in collaboration with Kepahiang's natural tourism potential, while simultaneously fulfilling social, entertainment, cultural identity, and economic functions for the local community.